DINAMIKA PASCA ARAB SPRING - Muhammad Syaroni Rofii (Universitas Jenderal Ahmad Yani, 2019)
The civil war that occurred in Syria shows a humanitarian tragedy in the twenty-first century.This conflict originally was part of a dynamic in democratic transition but turned into a prolonged civil war. It can be concluded that the cause of this tragedy is none other than because of a proxy war involving big countries. In this research, it was found that the failure of peace in Syria is inseparable from the influence of the big powers who use their influence to block any vetos related to Syrian crisis in United Nations. Each external actors attempt to protect their national interests and agendas at the same time reduce universal values. Conflict in Syria involving Rusia on one hand and the United States on other hand. Both coutries have different plan toward regime change in Syria which lead to other dimension of proxy war in contemporary world. This article attempted to explore the pattern of proxy war in Syria and its influence toward the stability of the region.